Multilocus Sequence Typing Tool for Cyclospora cayetanensis - Guo, Yaqiong (Emerg Infect Dis, 2016)
Because the lack of typing tools for Cyclospora cayetanensis has hampered outbreak investigations, we sequenced its genome and developed a genotyping tool. We observed 2 to 10 geographically segregated sequence types at each of 5 selected loci. This new tool could be useful for case linkage and infection/contamination source tracking.